Zuhud dan Signifikansinya terhadap Modernitas (Pemikiran Abu Al-Qasim Al-Qusyairi dalam Kitab Risâlat Al-Qusyairiyat Fî ’ilmi Al-Tashawwuf ) - Muhtadin, Muhtadin (Indonesian Journal of Islamic Theology and Philosophy, 2020)
one of the morals of the Prophet Muhammad peace be upon him, was Zuhud. this trait teaches that the world does not become the final destination of life, but rather as a means to worship and reach the passion of God Almighty. But unlike the case with modern life today, for him wealth and power as the main purpose of life, so that there is a drought of spiritual values in life. The purpose of this study is to uncover how important zuhud is in the modern life of Abu Al-Qasim Al-Qusyairi's perspective, this research uses descriptive, historical, verstehen, comparative and deduction methods. This research produces findings, that epistemologically, the concept of zuhud Abu Al-Qasim Al-Qusyairi rests on zuhud as morality and zuhud as maqâmat. A zahid must first take the maqam al-taubah, al-mujâhadah, al-khalwah wa al-‘uzlah, al-taqwâ, al-wara ’, then only al-zuhd. furthermore the concept of zuhud is very significant to be practiced in the life of modern society, because zuhud teaches humans not to be enslaved to the world, and advocates to put wealth in the hand only, but the heart is only adhered to Allah SWT, so that there will emerge the nature of social care, and create calm and happiness born and mind.